За пределом жестокости - Леонов Николай Иванович (МУРу - 90 лет, 2014)
Экземпляры: ф-14 (20220409) / Инвентарный номер: 57964 / Цена: 108.00 / Сис.шифр: Р2 / Авт.знак: Л 47 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6